1986
DOI: 10.1093/ptj/66.5.677
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Four Instruments for Measuring Lumbar Spine and Pelvic Positions

Abstract: We studied the between-therapist reliability and the validity of four instruments in measuring lumbar spine curvature and pelvic tilt. The four instruments and their measurements were 1) a tape measure to measure the change in lumbar curvature during trunk flexion; 2) a gravity goniometer to measure pelvic angle and lumbar curvature during stance, trunk flexion, and trunk extension; 3) a parallelogram goniometer to measure lumbar curvature during stance, trunk flexion, and trunk extension; and 4) a standard go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 13 publications
2
48
1
Order By: Relevance
“…Several studies report varying reliability from low [4,21,32,41] to high [14,20,28,31,44]. Within our study, we did not find any statistically significant correlation between the modified Schober test and MRI findings.…”
Section: Mobility Testscontrasting
confidence: 57%
See 2 more Smart Citations
“…Several studies report varying reliability from low [4,21,32,41] to high [14,20,28,31,44]. Within our study, we did not find any statistically significant correlation between the modified Schober test and MRI findings.…”
Section: Mobility Testscontrasting
confidence: 57%
“…Within our study, we did not find any statistically significant correlation between the modified Schober test and MRI findings. Clinical studies have found the reliability of the FTFD ranging from low [31] to high [4,15,19,39]. In our study, the relationship between structural changes of the lumbar spine and the FTFD was only weakly correlated to endplate changes on level L4-5.…”
Section: Mobility Testsmentioning
confidence: 48%
See 1 more Smart Citation
“…This method consists of measuring the shoulder flexion angle between the person's upper arm and midline of the trunk (person against the wall) with a standard manual goniometer. Other types of goniometer such as modified gravity goniometer and parallelogram goniometer were also used for measuring lumbar spine and pelvic positions in the sagittal plane [52]. The intra and inter-rater reliability of these different types of goniometer was similar and was moderate to good (ICCs > 0.50) for most posture indices measured with these tools (Table 1 …”
Section: Direct Body Measurements By Goniometry and Inclinometersmentioning
confidence: 99%
“…Back Range of Motion (lumbar flexion) was measured because of its common inclusion in disability determination. The measure was assessed using a gravity goniometer (Burdett et al, 1986) and mean lumbar flexion over two trials was calculated.…”
Section: Biomedical Constructs Andmentioning
confidence: 99%